2013
DOI: 10.1097/wno.0b013e31829c510e
|View full text |Cite
|
Sign up to set email alerts
|

Spectral-Domain Optical Coherence Tomography of Retinal Nerve Fiber Layer Thickness in NMO Patients

Abstract: RNFL in NMO is not different enough to distinguish NMO ON from MS ON eyes, but the intereye difference in RFNL with a history of unilateral ON may be a better diagnostic marker for NMO.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
35
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(42 citation statements)
references
References 18 publications
4
35
1
2
Order By: Relevance
“…However, Lange et al. () found that NMOSD‐ON patients did not have significantly thinner pRNFL than MS‐ON patients (63.7 versus 73.9 μ m, p = 0.56) in a study analysing the subset of patients with one ON episode. In addition, Outteryck et al.…”
Section: Discussionmentioning
confidence: 95%
“…However, Lange et al. () found that NMOSD‐ON patients did not have significantly thinner pRNFL than MS‐ON patients (63.7 versus 73.9 μ m, p = 0.56) in a study analysing the subset of patients with one ON episode. In addition, Outteryck et al.…”
Section: Discussionmentioning
confidence: 95%
“…In the past 15 years, the potential role of optical coherence tomography (OCT) measurements as biomarkers of disease progression in neurodegenerative disorders, particularly multiple sclerosis, Alzheimer's disease, neuromyelitis optica and Parkinson's disease, has been widely investigated [14][15][16][17][18][19][20][21][22][23][24]. OCT measurements are frequently used in observational studies, clinical practice and, more recently, therapeutic trials, with the number of studies in this area increasing exponentially over the last 5 years [21,25].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with NMO are, however, more likely to have bilateral optic neuritis at presentation and to present with worse visual acuities 18. There is a suggestion that there is greater thinning of the retinal nerve fibre layer in NMO on optical coherence tomography but this difference does not separate the conditions clinically at the time of presentation 23 24…”
Section: Mimicsmentioning
confidence: 99%